YouTube as Alternatif Media Learning in Vocational Education: A Systematic Literature Review - Suhanto; Rifai, Moch; Suprapto, Yuyun; Harianto, Bambang Bagus; Rossydi, Ahmad (Universitas Pendidikan Ganesha, 2024)
YouTube serves as a valuable alternative learning platform in education that offers a variety of instructional videos to improve learning outcomes. YouTube positively influences student learning by increasing skills, competence, motivation, and level of engagement in learning. YouTube's diverse content, accessibility, and engaging format make it a rich and enjoyable learning resource, especially when integrated into an excellent pedagogical context. YouTube is also expected to become an alternative learning media in education, especially vocational education and training. Therefore, it is necessary to review journals that discuss YouTube as an alternative learning media for vocational education. The method used in this research is a systematic literature review of journal papers published from 2017-2024. Journal articles came from three database sources, namely Scopus, Google Scholar, and Crossref, with search results of 2,157 journal articles; then, four stages of systematic literature review were carried out, with the final result being 86 research articles from related journals. The findings of this research are as follows: First, YouTube is recognized as an effective medium for learning, providing the ability to adapt, personalize, and develop autonomy and critical thinking. Second, instructional videos mediate vocational skills and facilitate vocational learning, incredibly interactive services. Third, YouTube has proven to be a very effective learning medium for practical competencies, providing a more accessible and more precise understanding of concepts. These conclusions highlight the value and potential of YouTube as a digital resource for continuing education and vocational learning.